Alimentación como recurso terapéutico en paciente con ansiedad y depresión - Pérez Reyes, Micaela Salomé (2023)
ABSTRACT. Introduction: Healthy eating is crucial to prevent diseases, observing a strong relationship between diet and mental health, research supports that a balanced diet can promote a better mood; However, there are still gaps in knowledge regarding this relationship, opening the door to more personalized interventions to increase the quality of life of patients with these conditions. Objective: The proposed research work was carried out to raise awareness of the importance of healthy eating as a therapeutic treatment in patients with anxiety and depression, as well as to document bibliographically, through an exegetical search of scientific evidence, the relationship between diet and these mental disorders. Methodology: A descriptive, qualitative and documentary research was used, the design focused on the bibliographic review with qualitative orientation; To collect the information with scientific validity, search managers were used, selecting 25 bibliographic references that met the inclusion criteria. Discussion: The discrepancy in the analyzed information may arise due to the type of study and methodology used in each publication, as well as the context in which they were carried out; Most research finds that dietary intervention can be an effective therapy for these disorders. Conclusion: Scientific evidence supports those dietary patterns such as the Mediterranean diet, consumption of vegetables, lean proteins, unsaturated fats, omega-3, vitamins and folates, significantly improve the clinical status of anxiety and depression disorders. Keywords: diet, mental health, depression and anxiety, treatment.